The Role of Sexual Taboos in Explaining Premature Ejaculation in Men: The Mediating Role of Intrusive Memories and Personality Traits - Abbasi, Reza; Rajabi, Soran; Amini, Naser (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to examine the role of sexual taboos in explaining premature ejaculation in men, with the mediating roles of intrusive memories and personality traits. In terms of nature, this study was applied–descriptive, and methodologically, it employed a correlational–regression design using structural equation modeling. For sample selection, a convenience sampling method combined with a snowball approach was used. The statistical population consisted of all married men or those with a stable sexual partner, aged 25 to 45 years, residing in Bushehr. From this population, 170 participants were voluntarily and conveniently selected. This sample size was determined based on the statistical requirements of structural equation modeling with a 95% confidence level. Data collection was conducted using the Sexual Taboo Beliefs Questionnaire by Abbasi and Kashkooli (2019), the Intrusive Memories Questionnaire by Clohessy and Ehlers (1999), the Big Five Personality Questionnaire by Gosling et al. (2003), and the Premature Ejaculation Diagnostic Questionnaire by Symonds et al. (2007). Data analysis was performed using descriptive and inferential statistics, including correlational–regression methods, via SPSS version 27. Path analysis was conducted using AMOS version 22. The results indicated that sexual taboos had a significant direct effect on premature ejaculation (β = 0.023, p = 0.045). Intrusive memories also played a significant mediating role in the relationship between sexual taboos and premature ejaculation (β = 0.027, p = 0.002). Furthermore, personality traits demonstrated a significant mediating effect in this relationship (β = 0.016, p = 0.001). The findings showed that intrusive memories increased the direct effect coefficient of sexual taboos on premature ejaculation from 0.23 to 0.27, whereas personality traits reduced this coefficient from 0.23 to 0.16. These results suggest that intrusive memories act as an amplifying factor, while personality traits function as a mitigating factor in the impact of sexual taboos on male sexual performance.